Peran Badan Kesatuan Bangsa Dan Politik (Kesbangpol) Provinsi Sumatera Barat Dalam Mencegah Korupsi - Irma Cahyani; Zahra, Muthia Julian; Annur, Raudhatul Natasya; Kusuma , Kencana Firjatullah; Hanoselina, Yulia; Helmi, Rahmadhona Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This study aims to examine the role of the National Unity and Politics Agency (Kesbangpol) of West Sumatra Province in preventing corruption. Using qualitative methods, data were obtained through interviews and policy analysis. Kesbangpol has played a role in increasing public awareness of the dangers of corruption through political education programs and strengthening national insight. However, the main challenge still lies in the practice of money politics and gratiﬁcation that damage democracy and reduce public trust in the government. Internally, Kesbangpol implements online attendance policies and wealth reporting to increase transparency and prevent corruption among employees. This study concludes that public administration ethics are very important in efforts to create clean and effective governance.